PENERAPAN MODEL COOPERATIVE LEARNING TIPE PICTURE AND PICTURE PADA MATA PELAJARAN PENDIDIKAN PANCASILA MATERI MENGENAL LAMBANG SILA-SILA PANCASILA KELAS 1 DI SD NEGERI 006 PALEMBANG - Dewi Kartika Sari; Septia Nur Safin; Melatri Octami; Femiseri Ardila Ketriani; Panggar Dwi Anata; Dira Sagita; M.Arta Bahri; Selma Kristianti; Inka (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low ability of first-grade students at SD Negeri 006 Palembang to recognize the symbols of the Pancasila principles and the less-than-optimal student engagement in a teacher-centered learning process. The purpose of this study was to describe the implementation of the Cooperative Learning Picture and Picture model in Pancasila Education on the topic of recognizing the symbols of the Pancasila principles and to determine its impact on students’ learning activities and understanding. This study employed a qualitative approach using a descriptive method. The research subjects consisted of 28 students from Class I-B of SD Negeri 006 Palembang, including 14 male students and 14 female students. Data were collected through observation, documentation, and field notes. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings revealed that the implementation of the Cooperative Learning Picture and Picture model was able to improve students’ activeness, enthusiasm, and cooperation during the learning process. The use of picture media and Pancasila symbol puzzles helped students understand the material in a more concrete, interesting, and meaningful way. Students found it easier to recognize, match, and remember the symbols of the Pancasila principles through group discussions and collaborative picture-arranging activities. Therefore, the Cooperative Learning Picture and Picture model can serve as an effective alternative learning strategy to improve the quality of Pancasila Education learning in elementary schools.